Ectodermal Dysplasia in child: multidisciplinary management - Schautz, Caroline Guimarães; Silva, Larissa Conrado da; Faker, Khawana; Tostes, Mônica Almeida; Cancio, Viviane (Brazilian Dental Science, 2019)
Ectodermal Dysplasia (ED) represents a group of hereditary conditions in which anatomical structures derived from the ectoderm show defects in its development. It is observed aplasia or hypoplasia of the tissues, among them the changes of dental relevance, as the anomalies regarding the number and morphology of the teeth. Due to the particularity of the cases, the dental surgeon must adapt the operative techniques and the choice of dental materials to each individual, according to the perceived need and condition. The objective of the present study is to report the clinical case of a 10 - year old male patient with ectodermal dysplasia who was attended in the discipline of Patients with Special Needs of Dentistry of the Federal University of Fluminense and its multidisciplinary aspects.KeywordsChildren with disabilities; Dental care for disabled; Ectodermal dysplasia; Oral rehabilitation.